The effect of household income and consumption on family welfare with lifestyle as a moderating variable - Ageng Nugroho; Otti Wulandhari (International Journal of Applied Finance and Business Studies, 2023)
The agricultural exchange rate (NTP) as an indicator of farmers' income per year tends to increase, this sector also absorbs Indonesian labor, but why poverty as an indicator of welfare lies with farmers. This study aims to determine whether there is an effect of income on welfare, whether household consumption affects welfare, whether lifestyle moderates the relationship between income and welfare. Nor moderate the relationship between consumption and welfare. The study was conducted on 100 samples representing 9,546 households in Majasari District, Pandeglang Regency, Banten. This research uses a quantitative approach with a causal descriptive model. After statistical analysis with SEM-Pls, it was revealed that there is a positive effect of income on welfare. This can be seen from the significant value of 0.036 below 5% (0.05), and the T-Statistics value of 2.092 exceeds the T-table (1.96). In the analysis it was also found that there was a positive effect of consumption on welfare, it was seen that a significant value of 0.002 was below 0.05 and the T-statistic value of 3.107 exceeded the T-table of 1.96. In this study, lifestyle was not found to moderate the relationship between income and welfare, this can be seen from the T-statistic value of 0.274 (above 1.96) and a significance value of 0.784 (above 0.05). In this study, there was no moderating effect of lifestyle on well-being, this was indicated by the T-count value of 0.296 (greater than 1.96), a significance value of 0.767 (greater than 0.05).